2016
DOI: 10.3390/ijerph13070675
|View full text |Cite
|
Sign up to set email alerts
|

Air Pressure, Humidity and Stroke Occurrence: A Systematic Review and Meta-Analysis

Abstract: Background/Aims: An influence of climate upon stroke risk is biologically plausible and supported by epidemiological evidence. We aimed to determine whether air pressure (AP) and humidity are associated with hospital stroke admission. Methods: We searched MEDLINE, Embase, PsycINFO, CINAHL, Web of Science, and GEOBASE, from inception to 16 October 2015 to identify relevant population-based observational studies. Where possible, data were pooled for meta-analysis with odds ratios (OR) and corresponding 95% confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 31 publications
1
23
2
Order By: Relevance
“…Fifteen million stroke events are recorded annually by the World Health Organization, leading to disability in many patients and placing a large economic burden on society. In addition to well-established major stroke risk factors, several studies have elucidated the influence of weather elements on stroke incidence [1,2]; however, the complex association of weather and stroke remains unclear. The inconsistency of the results arises from various factors: such as studying different climate zones, lacking subdivision of ischemic stroke events according to their etiology, small patient numbers, and also a selection bias of stroke centers involved in the studies [1,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Fifteen million stroke events are recorded annually by the World Health Organization, leading to disability in many patients and placing a large economic burden on society. In addition to well-established major stroke risk factors, several studies have elucidated the influence of weather elements on stroke incidence [1,2]; however, the complex association of weather and stroke remains unclear. The inconsistency of the results arises from various factors: such as studying different climate zones, lacking subdivision of ischemic stroke events according to their etiology, small patient numbers, and also a selection bias of stroke centers involved in the studies [1,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous literatures have well explored the independent effects of temperature or humidity on human health [ 8 , 10 ]. However, there are limited studies on their joint effects, particularly in a developing country such as China [ 9 , 11 , 12 ]. Some previous studies found that the magnitude of effect estimates on mortality for cold temperatures was increased from the north to the south in China [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Higher incidences of stroke, unspecified cardiac and asthma mortalities have all been associated with a drop in minimum temperature [74][75][76][77]. Strokes have also been associated with a decrease in pressure, findings of which are supported in numerous meta-analytical studies [78,79], while asthma disease has been associated with a decrease in pressure [80]. Within the African context, diarrhoeal morbidity and mortality is associated with rainfall [81].…”
Section: Discussionmentioning
confidence: 99%